Are the Teachers and Students Satisfied: Sustainable Development Mode of Entrepreneurship Education in Chinese Universities? - Huang, Yangjie; Liu, Lanying; An, Lanyijie (Frontiers in Psychology, 2020)
Entrepreneurship education plays an important role in sustainable development. Chinese governmental agencies are making all-out efforts to promote schoolwide entrepreneurship education from top to bottom to achieve sustainable economic and social development. This is a phenomenon worth studying and summarizing. Improving the satisfaction degree of teachers and students of entrepreneurship education in universities for the sustainable development become typical mode of Entrepreneurship Education in Chinese Universities. The data is derived from 12,269 valid questionnaires in student volume and 1,241 valid questionnaires in teacher volume from top universities in China, and regression and variance analysis were applied. The results show that the overall satisfaction of teachers and students is higher than the national average. There are significant differences in the overall satisfaction of different types of teachers and students. Teachers are most satisfied with the organizational leadership measures of the universities in entrepreneurship education, and the least satisfied with the lack of professional human resource management strategies for entrepreneurship education teachers. Students are most satisfied with entrepreneurship policy and least satisfied with entrepreneurship learning, especially that entrepreneurship theory learning and practice learning are closely combined with students' major. The overall satisfaction of students of entrepreneurship education mainly comes from the influence of "entrepreneurship policy dividend", entrepreneurship learning, entrepreneurship competition and entrepreneurship practice go hand in hand. The overall satisfaction of teachers is most affected by the satisfaction of organizational leadership, followed by the satisfaction of mechanism guarantee and teaching management. This study introduces the sustainable development model of entrepreneurship education in Chinese top universities through the improvement of satisfaction of entrepreneurship education, and has certain reference significance for managers and teachers of entrepreneurship education practice in other developing countries.